2011
DOI: 10.1002/lt.22274
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative estimation of the liver graft weight in adult right lobe living donor liver transplantation using maximal portal vein diameters

Abstract: An accurate preoperative estimate of the graft weight is vital to avoid small-for-size syndrome in the recipient and ensure donor safety after adult living donor liver transplantation (LDLT). Here we describe a simple method for estimating the graft volume (GV) that uses the maximal right portal vein diameter (RPVD) and the maximal left portal vein diameter (LPVD). Between June 2004 and December 2009, 175 consecutive donors undergoing right hepatectomy for LDLT were retrospectively reviewed. The GV was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
0
24
1
1
Order By: Relevance
“…In our review, we found that currently there are 16 published formulas for estimating SLV in the worldwide literature4‐18 (see Table 1). More recently, several authors have combined portal vein diameters and SLV estimates to calculate the hemiliver volume for split liver transplantation or LDLT 21, 22. In our clinical experience, SAIP volumetric studies using CT scans (ie, software‐assisted CT scans) have been very accurate in predicting graft sizes with predetermined resection planes in comparison with actual graft volumes in living liver donors 23.…”
Section: Various Formulas Used For Estimating Slvmentioning
confidence: 99%
“…In our review, we found that currently there are 16 published formulas for estimating SLV in the worldwide literature4‐18 (see Table 1). More recently, several authors have combined portal vein diameters and SLV estimates to calculate the hemiliver volume for split liver transplantation or LDLT 21, 22. In our clinical experience, SAIP volumetric studies using CT scans (ie, software‐assisted CT scans) have been very accurate in predicting graft sizes with predetermined resection planes in comparison with actual graft volumes in living liver donors 23.…”
Section: Various Formulas Used For Estimating Slvmentioning
confidence: 99%
“…In our review, were found at least 11 different 2 , 3 , 4 , 6 , 7 , 8 , 9 , 11 , 12 , 17 , 18 , 21 , 22 , and sometimes conflicting, mathematical formulas aiming to predict graft size. Some of these methods do not use the computed tomography volumetry, but body surface area, and the diameter of the portal vein and/or their branches.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum graft size required for LDLT to provide adequate hepatic function has been reported to be a SLV of 40% or GRWR of 0.8 [2]. For insufficient graft volume, APOLT was established to increase liver volume after LT [19], although there are some limitations in the choice of recipients.…”
Section: Discussionmentioning
confidence: 99%
“…A small-for-size graft is defined as a graft to recipient weight ratio (GRWR) less than 0.8 or a ratio of graft weight against standard liver volume (SLV) less than 40% [1,2], and these grafts result in a high mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%